How does machine translation and post-editing affect project management? An interdisciplinary approach - Plaza-Lara, Cristina (Universidad de Córdoba, 2020)
Machine translation (MT) and post-editing (PE) are two services that are increasingly in demand in the translation industry. In a context in which large-scale projects are required within tight deadlines, the deployment of this technology to increase productivity is a reality. However, this increase in productivity can only be achieved with appropriate management of the project: MT must not be understood as a tool, but as a process, and project managers, who are usually responsible for the project from start to finish, have to cope with new MT and PE workflows that pose different challenges. Although much has been written about the use of MT and PE in professional practice(resulting in different lines of research in this field), little attention has been paid to the role of the project manager in MT and PE projects. For this reason, the main objective of this paper is to analyse how MT and PE affect the factors that project managers must keep in mind when managing projects, taking as a starting point the most important reference frameworks in project management. The main objective is to offer an interdisciplinary perspective that explains the new challenges the industry is facing and how these challenges affect the different stakeholders involved in the project.
Keywords: Traducción automática; Posedición; Gestión de proyectos; Interdisciplinariedad; Desafíos de la industria de la traducción